F-CHILS maps - a novel encryption scheme for secured medical data transmission using FoG-ban environment. (14th June 2022) - Amudha, S.; Murali, M.
With internet of things (IoT), remote health monitoring plays an effective role in human disease diagnosis. The gathered patient health information from sensors is transferred to the medical physician, care givers and medical centre in remote mode. Even though different solutions have been proposed, to prevent security issues, malicious user's involvement, timely delivery and also to ensure data integrity, high-end security algorithms are needed. Many traditional algorithms were incorporated in the IoT network with low power and memory requirements. But these algorithms can be easily broken and affected by several attacks due to the poor mathematical operations. Hence new hybrid 3D-chaotic maps FoG-based chaotic Henon integrated logistic-tents schemes used for key generation for crypto graphical operations are proposed. These 3D hybrid chaotic maps are hard to break and have been evaluated by extensive experimentations. Proposed 3D-chaotic maps have significantly increased the security of the clinical data when compared with conventional algorithms.